2008
DOI: 10.1021/ma800015g
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Neutron Scattering of a Solvent-Swollen Segmented Polyurethane as a Probe of Solvent Distribution and Polymer Domain Composition

Abstract: Segmented polyurethanes consist of alternating rigid aromatic (hard) and flexible (soft) segments that phase separate into hard and soft segment-rich nanodomains. The domain structure results in what has been presumed to be an extended, cross-linked network, giving these materials unique mechanical properties. Because of poor contrast and volume fractions of the discontinuous phase, previous scattering studies have focused on polyurethanes with hard segment contents greater that 30 wt %. This study focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The increase in sol fraction in 25 CPPUF can dissipate the applied stress. Moreover, the hard domains in a polyurethane matrix are considered to function similar to that of fillers that are connected with the lamellar matrix by entanglements . It has been shown that when spheroid fillers are used to reinforce a polymer, it is the degree of interaction between the filler and the polymer matrix that contributes to the mechanical properties .…”
Section: Resultsmentioning
confidence: 99%
“…The increase in sol fraction in 25 CPPUF can dissipate the applied stress. Moreover, the hard domains in a polyurethane matrix are considered to function similar to that of fillers that are connected with the lamellar matrix by entanglements . It has been shown that when spheroid fillers are used to reinforce a polymer, it is the degree of interaction between the filler and the polymer matrix that contributes to the mechanical properties .…”
Section: Resultsmentioning
confidence: 99%
“…Based on TEM and FTIR observation, we select a fluid model to extract quantitative information of hard domains from SANS traces [Figure (a)] of foams. This model envisages discretely dispersed hard sphere morphology in a continuous soft matrix . We estimate the long range periodicity between hard domains as 18.7 nm, the volume fraction of hard domains as 0.157 and average domain size as 30 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The SSs are polymers (oligomers) of the ester of adipic acid with 1,4 butanediol; they have an average molecular weight in the range of 800 to 1050 Da [9]. The HSs consist of very short polyurethanes made from 4,4#-diphenylmethane diisocyanate molecules bonded together by urethane links to the butanediol that serve as chain extenders, as shown in Figure 1.…”
Section: Experimental Section 21 Materialsmentioning
confidence: 99%
“…Since Estane 5703 strongly affects the mechanical properties of the composites, it is essential to know how the material changes with time at various environmental conditions. Small-angle scattering technique is a very powerful tool for investigating internal structures of PUs [2,[4][5][6][7][8][9]. Mang and coworkers [2,9] applied small-angle neutron scattering (SANS) technique to determine the domain structures in deuterated Estane with low HS content.…”
Section: Introductionmentioning
confidence: 99%